PENGEMBANGAN INTERVENSI UNTUK TINGKAT PEKERJA DAN TIM KERJA MELALUI GAMES DAN SIMULASI - Fatonah, Umi (Jurnal Teknologi Pendidikan, 2017)
One of the ways used in order to develop people is through training. A training program may include three things, technical training can improve the skills. A lesson can be declared a success if the behavior changes, increased knowledge, and expertise increases. In developing interventions to increase the performance of the employee one of them is through simulations and games. Learning with simulations and games can increase the interest and motivation of the study, because by using the method of simulation and game of student involvement is more dominant, participants can directly interact with learning situations real, besides learning with simulations and games can give you a good understanding of participants, so it can be concluded that the games and simulation is an effective tool in learning and performance interventions employees.